Description of Hemodynamic Changes in Section Caesarea Patients with Spina; Anesthesia in Sijunjung Regional General Hospital - Nofyanto, Deden; Sukmaningtyas, Wilis; Triyudono, Danang (Java Nursing Journal, 2024)
Background: Every anesthetic action must Background: Every anesthetic action must pay attention to the patient's condition because this anesthetic action causes effects on all body systems, including hemodynamic changes in the patient's body. To see if there are hemodynamic changes that occur, blood pressure and pulse monitoring can be done during the Sectio Caesarea surgery process. Purpose: to know the description of hemodynamic changes in Sectio Caesaria patients with spinal anesthesia at Sijunjung Regional General Hospital. Methods: The type of research used is observational research with descriptive research type. The population in this study were all patients with cesarean section with spinal anesthesia at the Sijunjung Regional General Hospital in July - August with a sample size of 20 patients. Research instruments used ECG monitors and observation sheets using descriptive data analysis. Findings: blood pressure and pulse of respondents before spinal anesthesia were seen entirely, namely 20 respondents (100%) with normal blood pressure and pulse and after spinal anesthesia as many as 14 people (70%) experienced hypotension and 6 respondents (30%) with normal blood pressure. While the pulse rate in respondents after spinal anesthesia was 11 people (50%) experiencing tachycardia and 9 people (45%) with a normal pulse. Conclusion: then it means that there is a picture of hemodynamic changes in sectio caesaria patients with spinal anesthesia at the Sijunjung Regional General Hospital.